Caveolin‐1 as a promoter of tumour spreading: when, how, where and why. Issue 3 (23rd March 2013) - Senetta, Rebecca; Stella, Giulia; Pozzi, Ernesto; Sturli, Niccolo; Massi, Daniela; Cassoni, Paola
Abstract Caveolae are non‐clathrin invaginations of the plasma membrane in most cell types; they are involved in signalling functions and molecule trafficking, thus modulating several biological functions, including cell growth, apoptosis and angiogenesis. The major structural protein in caveolae is caveolin‐1, which is known to act as a key regulator in cancer onset and progression through its role as a tumour suppressor. Caveolin‐1 can also promote cell proliferation, survival and metastasis as well as chemo‐ and radioresistance. Here, we discuss recent findings and novel concepts that support a role for caveolin‐1 in cancer development and its distant spreading. We also address the potential application of caveolin‐1 in tumour therapy and diagnosis.